The Role of Biomarkers in the Diagnosis and Prognosis of Ovarian Cancer: A Comprehensive Review - Tariq, Shazia Sohail (Biological and Clinical Sciences Research Journal, 2025)
Ovarian cancer remains one of the most lethal gynecologic malignancies owing to its often-asymptomatic nature and late-stage diagnosis. Biomarkers have emerged as critical tools in early detection, risk stratification, and prognostication. This review provides an in-depth analysis of the current landscape of biomarkers in ovarian cancer, addressing both diagnostic and prognostic roles. We explore classical biomarkers such as CA125 and HE4 and novel biomarkers including circulating tumor cells, microRNAs, and genomic signatures. In addition, we discuss advances in multi-marker panels and liquid biopsy approaches, underscoring the importance of integrating biomarker data with clinical parameters to guide personalized management. Limitations, challenges, and future perspectives are discussed, emphasizing the need for further validation in large, prospective trials. This comprehensive review integrates over 30 recent references to offer clinicians and researchers a robust resource for understanding and applying biomarker data in ovarian cancer management.